Cover Image. (19th August 2022) - Hui, Pui Wah; Pang, Polly; Tang, Mary H. Y.
Abstract : The cover image is based on the Original Article 20 years review of antenatal diagnosis of haemoglobin Bart's disease and treatment with intrauterine transfusion by Pui Wah Hui et al., https://doi.org/10.1002/pd.6125 .